Influence of Environmental Design on Team Interactions Across Three Family Medicine Clinics: Perceptions of Communication, Efficiency, and Privacy. (October 2019) - Karp, Zaher; Kamnetz, Sandra; Wietfeldt, Natalie; Sinsky, Christine; Molfenter, Todd; Pandhi, Nancy
Objective: In this study, we explored how two different primary care clinic physical layouts (onstage/offstage and pod-based [PB] designs) influenced pre- and postvisit team experiences and perceptions. Background: Protocols encourage healthcare team communication before and after primary care visits to support better patient care. Physical clinic environments may influence these behaviors, but limited research has been performed. Method: We conducted observations, three interviews with clinic managers, and six focus groups with 21 providers and staff at three family medicine teaching clinics. Observational data were captured through field notes and spaghetti diagrams. Interviews and focus groups were recorded, transcribed, and analyzed using a grounded theory-based approach to understand how aspects of the clinic environment affected communication, efficiency, and privacy. Results: Variations in communication styles and trade-offs between patient contact and privacy emerged as differences. In the onstage/offstage design, colocated teams had increased verbal communication but perceived being isolated from other clinic teams. In contrast, teams in PB clinics communicated with other clinic teams but had more informal patient contact within care-team stations that imposed privacy risk. Conclusions: Primary care clinic design appears to alter provider–team and patient–provider communication and flow. Organizations should consider aligning environmental design with desired interaction patterns when building new primary care clinics.